A REVIEW ON PAST AND PRESENT STATUS OF MEDICAL EDUCATION SYSTEM (International Journal of Ayurveda and Pharma Research, 2018)
The origin of medical education dates back to era of starting of Hindu civilization. The Vedic literature can be called as the source of all medical education systems. Amongst them Ayurveda is that science which has give emphasize on holistic approach towards health. Surprisingly the modalities for a learner of medical science have been well described in the texts of Ayurveda. The present situation is somehow different regarding the status of medical education all over the world. So, this study has been conducted to show the glorious approaches as present in ancient medical education system which can revive the present scenario and status of medicinal education. Materials & Methods: The excessive texts of Ayurveda have been studied and critically analyzed to identify the status of medical education as described. Simultaneously the present states of contemporary medical education been studied. The demerits have been tried to evaluate & along with that some solution have been shown which may be helpful to change the present scenario of medical education throughout the world. Results: The result shows that the approach with the basic principle of Ayurveda can modify or resolve the problems as arises in modern medical educational system. Conclusion: Therefore, it can be proposed that a collaborative approach is the need of time to solve all the obstacles so that medical educational system can be updated & become more beneficial for the society.